Synthesis and Biological Activity of New Hydrazones Based on N-Aminomorpholine - Nurkenov O. A. Oralgazy; Zhautikova S. B. Saule; Khlebnikov A. I. Andrey Ivanovich; Syzdykov A. K. Ardak; Fazylov S. D. Serik; Seilkhanov T. M. Tulegen; Kabieva S. K. Saule; Turdybekov K. M. Kobylandy; Mendibayeva A. Z. Anel; Zhumanazarova G. M. Gaziza (2024, 2024)
Title screen